Enhancing Parental Coping with a Child's Heart Condition: A Co-production Pilot Study. Issue 4 (1st October 2020) - Jackson, Alun C.; Frydenberg, Erica; Koey, Xui Min; Fernandez, Amanda; Higgins, Rosemary O.; Stanley, Tracy; Liang, Rachel Pui-Tak; Le Grande, Michael R.; Murphy, Barbara M.
ABSTRACT: Families of children with congenital heart disease (CHD) can have difficulties coping with the stress of their child's condition and would benefit from assistance to cope better. To address the needs of these parents, the Australian Center for Heart Health/HeartKids Australia/Melbourne Graduate School of Education co-produced Family Coping Project was initiated. This project involved two systematic literature reviews, interviews with parents of children with CHD, and the development and piloting of a manualised parental coping program. The primary aims of the pilot study were to determine whether the program would: attract high needs families; enhance the coping self-efficacy of parents; and be acceptable to parents in terms of content and mode of delivery. The secondary aims were to investigate whether the program would impact on parental coping, parental stress and general stress. Parents completed pre-, post-program and 6-month follow up assessment measures, with parent stress scores being compared to stress scores reported for other chronic condition parent carer groups. Twenty-one parents participated and provided baseline data. They were found to be significantly more stressed than other parent carer groups. Eleven parents completed post-program data and 13 completed 6-month follow-up data. There was a significant increase in parents' coping self-efficacy from pre- to post-program, and from pre- to 6-months. Parents' use of productive coping styles increased significantly from pre- to post-program. The program was rated as highly acceptable in terms of content and delivery mode. The pilot provides strong evidence for upscaling the program in conjunction with individualized psychological support for parents to extend knowledge acquisition and attitude change into enhanced coping skills and demonstrated the benefits of a co-production process.